المشروع التربوي الجزائري: بين الحداثة التربوية والأزمة التعليمية - شاوي, رندة (Changement Social, 2019)
تحتل مسألة التربية حيزا لا يُستهان به من الاهتمام في مجتمعنا، خاصة إذا كان التعليم يستمد أهميته منها باعتباره الورشة الفعلية لتصنيع النموذج الإنساني. وفي ظل التطور التقني وما فرضه من تغيرات لامست شتى المجالات بما فيها المجال التربوي حيث جعلت الوعاء التعليمي بحاجة إلى المساءلة الجذرية للبحث في الأسباب الفعلية لعطالة المنظومة التعليمية في نسقها الثقافي. وإن كان الكثير من الباحثين والمهتمين بهذا الشأن يوعزونها إلى الحداثة التربوية وما فرضته من استتباع ثقافي للآخر معتبرينها من أخطر المزالق الفكرية السائدة حول " المشروع التربوي الجزائري" لما فرضته من هيمنة الكثير من الأطر الإيديولوجية التبسيطية للإشكالية التربوية بمختلف أبعادها حيث تختزل الواقع  بأبعاده المتعددة والمتغيرة على حساب النظرة التقييمة للواقع الفعلي سواء كان ذلك على مستوى المرجعيات الفكرية الموجهة والمؤطرة مسبقا بفعل العولمة، أو من حيث منهجيات تحديد المشكلات و حلّها. وهذا ما جعلنا نتساءل عن واقع المشروع التربوي الجزائري بين الحداثة التربوية والأزمة التعليمية في ظل رهانات العولمة . الكلمات المفتاحية : المشروع التربوي – الحداثة التربوية – الأزمة التعليمية The issue of education occupies a considerable amount of attention in our society, especially if education derives its importance from it as the actual workshop for the manufacture of the human model. In light of the technical development and the changes that have taken place in various fields, including the educational field, the educational tool has required radical accountability to investigate the actual causes of the educational system's suspension in its cultural format. Although many researchers and those interested in this matter, they are referring to the modernity of education and the cultural imposition of the other as one of the most serious intellectual pitfalls prevailing on the "Algerian educational project" because of the imposition of the dominance of many of the simplistic ideological frameworks of the educational problem of various dimensions, reducing the reality in its multiple dimensions And changing at the expense of a realistic view of reality, whether at the level of intellectual references directed and pre-framed by globalization, or in terms of methodologies to identify and solve problems. This has made us wonder about the reality of the Algerian educational project between the educational modernity and the educational crisis under the bets of globalization